2011
DOI: 10.1002/jobm.201000223
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between carotenoids and sunlight response in members of the family Micrococcaceae

Abstract: The aim of this study was to compare the photoprotective effect of carotenoids in phylogentically related bacteria, which synthesize structurally different pigments. Two organisms were isolated from the same environment. Their 16S rDNA sequences and phenotypic characteristics identified them as members of the family Micrococcaceae. Reverse phase HPLC and absorption spectroscopy revealed that one of them, designated RMB40, synthesized 3 carotenoids with 9 conjugated double bonds, whilst the other, designated RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The biological function of carotenoids in nonphototrophic microorganisms is primarily in the roles of oxidative stress relief and membrane stability (Britton, 1995). As powerful antioxidants, carotenoid biosynthesis has been shown to respond to activated oxygen species under conditions such as high copper concentration, light irradiation and biofilm formation (Moraleda-Munoz et al, 2005;Takano et al, 2005;Pezzoni et al, 2011;Galbis-Martinez et al, 2012;Zheng et al, 2013). Carotenoids are often localized to cell membranes, where their influence on membrane fluidity is a function of the molecule's exact structure (Lutnaes et al, 2004;Gruszecki, 2009;Dieser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The biological function of carotenoids in nonphototrophic microorganisms is primarily in the roles of oxidative stress relief and membrane stability (Britton, 1995). As powerful antioxidants, carotenoid biosynthesis has been shown to respond to activated oxygen species under conditions such as high copper concentration, light irradiation and biofilm formation (Moraleda-Munoz et al, 2005;Takano et al, 2005;Pezzoni et al, 2011;Galbis-Martinez et al, 2012;Zheng et al, 2013). Carotenoids are often localized to cell membranes, where their influence on membrane fluidity is a function of the molecule's exact structure (Lutnaes et al, 2004;Gruszecki, 2009;Dieser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Light of different qualities could also influence cellular components, such as amino acids , pigments , and sterol content . Experiments on H. ostrearia demonstrated that light intensity and quality could regulate its pigmentation , and more cellular production was detected under BL .…”
Section: Introductionmentioning
confidence: 99%